Which epenthetic vowel? Phonetic categories versus acoustic detail in perceptual vowel epenthesis - Guevara-Rukoz, Adriana; Lin, Isabelle; Morii, Masahiro; Minagawa, Yasuyo; Dupoux, Emmanuel; Peperkamp, Sharon (The Journal of the Acoustical Society of America, 2017)
This study aims to quantify the relative contributions of phonetic categories and acoustic detail on phonotactically induced perceptual vowel epenthesis in Japanese listeners. A vowel identification task tested whether a vowel was perceived within illegal consonant clusters and, if so, which vowel was heard. Cross-spliced stimuli were used in which vowel coarticulation present in the cluster did not match the quality of the flanking vowel. Two clusters were used, /hp/ and /kp/, the former containing larger amounts of resonances of the preceding vowel. While both flanking vowel and coarticulation influenced vowel quality, the influence of coarticulation was larger, especially for /hp/.